The Inheritance Of A Wife Who Has Been Rejected And The Expiration Of Her Iddah Perspective Of Madhhab Imam Syafi'i (Case Study on the Mining Community of Mandailing Natal Regency) - Paijal Usrin Siregar; Mohammad Amir Bin Wan Harun (ISNU Sumatera Utara, 2024)
This study examines the inheritance rights of divorced wives whose iddah period has expired in the Tambangan Jae community, Mandailing Natal Regency, and analyzes the practice from the perspective of Imam Shafi'i's legal opinion. According to Imam Shafi'i, the expiration of the iddah period terminates the marital bond (al-zawjiyyah), thereby eliminating the reciprocal right of inheritance between former spouses. However, the customary practices of the Tambangan Jae community recognize inheritance rights for divorced wives even after the expiration of the iddah period. This research employs an empirical legal approach through field research using interviews with religious leaders, community leaders, and local residents. The collected data were analyzed using a qualitative descriptive method with a deductive approach. The findings reveal that the community continues to grant inheritance rights to former wives based on several considerations, including customary traditions, protection of women and children, recognition of the wife's contribution to acquiring family assets, and the need to ensure the welfare and education of the children. These practices differ significantly from Imam Shafi'i's opinion, which strictly limits inheritance rights to spouses whose marital relationship still legally exists. The study concludes that the community's practice is rooted primarily in social justice and local customary values rather than classical Islamic inheritance doctrine. Therefore, the protection intended for former wives and children would be more appropriately realized through the distribution of jointly acquired marital property rather than inheritance, a solution that is more consistent with Imam Shafi'i's legal reasoning as well as Indonesian positive law.